Late preterm babies and the risk of neurological damage - Ramenghi, Luca A. (Acta Biomedica Atenei Parmensis, 2015)
Late preterm infants (born between 34+0 and 36+6 weeks gestation) account for the recent striking increase in premature birth and they carry a higher vulnerability to suffer brain insults compared to term infants. These babies can develop any kind of known brain lesions including those affecting the most premature babies (i.e.an intraventricular haemorrhage) and lesions affecting more typically term babies like asphyxia and stroke. In other words there is not a specific brain lesion characterizing this gestational age group, and there is not a specific maturational landmark although “subplate neurons” are suppose to ultimate their connectivity in this period and the cortical volume is significantly increasing. In addition we should not forget the possibility that “late preterm babies” may present neurological clinical impairments in the absence of recognized morphological brain lesions even with the use of highly sophisticated MR imaging techniques. For these reasons a wider use of more sophisticated neuro radiological studies is not sufficient to better understand why some studies highlight that the risk of developmental delay or disability can reach 36% higher among late preterm infants compared with term infants. We believe we should improve also our skills to identify even those very subtle clinical signs of impairment deserving further investigations although we often admit these babies in the normal post natal nurseries where clinical observation cannot be so appropriate.